2021
DOI: 10.3390/su13169377
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Countermeasures and Passengers’ Confidence of Urban Rail Travel in Bangkok

Abstract: Rail transit systems around the world have been suffering from heavily reduced ridership due to reduced capacity for social distancing and passengers’ concern over the risk of COVID-19 infection. Various countermeasures were implemented to reduce the COVID-19 risk so that passengers felt safe to travel on rail. The objectives of this study were to evaluate COVID-19 countermeasures of Bangkok’s urban rail from passengers’ viewpoints and examine its influence on passenger’s confidence. The background of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…According to the findings, two factors, namely infection concern and wearing face masks, play a significant role in choosing a travel mode, followed by social distancing and cleanliness. The findings are in line with the previous studies reflecting the impacts perceived safety and concerns about being infected had on mode choice [74][75][76]. The effects of sociodemographic factors such as gender, car ownership, marital status, and job status on prioritizing pandemic-related items when selecting a mode of transportation were also studied.…”
Section: Discussionsupporting
confidence: 88%
“…According to the findings, two factors, namely infection concern and wearing face masks, play a significant role in choosing a travel mode, followed by social distancing and cleanliness. The findings are in line with the previous studies reflecting the impacts perceived safety and concerns about being infected had on mode choice [74][75][76]. The effects of sociodemographic factors such as gender, car ownership, marital status, and job status on prioritizing pandemic-related items when selecting a mode of transportation were also studied.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings indicated that 89.9% of participants expressed willingness to get vaccinated against COVID-19, whereas Kitro et al found that less than half of Thai people and expatriates living in Thailand were willing to get vaccinated against COVID-19 (41.8%) ( 39 ). A series of mobile health applications have been introduced by the healthcare sector and implemented to aid disease control monitoring and prevention of widespread outbreaks ( 14 – 16 ). However, the study showed that the use of those applications was relatively rare because of the low rate of digital literacy among Thai people ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…“New normal” guidelines refer to the requirement for Thai people to modify their behaviors and change their lifestyle patterns to prevent COVID-19 infection ( 11 13 ). Examples of such changes include working from home, covering the mouth when coughing and sneezing, wearing a cloth mask or surgical mask, maintaining a distance of at least 1 m from others, washing hands frequently, checking body temperature, self-assessment and tracing using the MorChana application (Ministry of Digital Economy and Society, Bangkok, Thailand) to track movements ( 14 ), checking in and checking out of visited locations using ThaiChana [“Thais win” in Thai language; Center for COVID-19 Situation Administration (CCSA), Bangkok, Thailand] ( 15 ), accessing vaccine services with Morprom (Ministry of Public Health, Bangkok, Thailand) ( 16 ), and businesses and services providing online instead of offline services to adapt to the current situation. Lifestyle changes to shift to a “new normal” mode may therefore be essential measures for the prevention of subsequent waves of COVID-19 and re-emergence in future outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Sweden showed a 40%–60% decrease in public transit ridership ( Jenelius and Cebecauer, 2020 ). In Bangkok, Thailand, the railway ridership reduced by 79% during April 2020 ( Vichiensan et al, 2021 ). In Hong Kong, China, people reduced their Metro Transit Railway use by more than 40% from January to March 2020 ( Zhang et al, 2021 ).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Low transit ridership could further lead to financial crises and operational difficulties. As many studies highlighted, fear of infection and unfavorable public views of transit services are the primary challenges for rebuilding transit riders' confidence ( Abdullah et al, 2021 ; Ashraf Javid et al, 2021 ; Hotle et al, 2020 ; Vichiensan et al, 2021 ). Given COVID-19 may remain a potential public health threat for a longer period of time than what might once have been expected, building trust and attracting riders back have become crucial priorities for Sun Metro and other transit providers.…”
Section: Introductionmentioning
confidence: 99%